Lycium barbarum Polysaccharide Prevents Focal Cerebral Ischemic Injury by Inhibiting Neuronal Apoptosis in Mice - Wang, Tengfei (Public Library of Science, 2014)
AIMS OF THE STUDY: To investigate the neuroprotective effect of Lycium barbarum polysaccharide (LBP) on focal cerebral ischemic injury in mice and to explore its possible mechanism. MATERIALS AND METHODS: Male ICR mice were used to make the model of middle cerebral artery occlusion (MCAO) after intragastric administration with LBP (10, 20 and 40 mg/kg) and Nimodipine (0.4 mg/kg) for seven successive days. After 24 h of reperfusion, neurological scores were estimated and infarct volumes were measured by 2, 3, 5-triphenyltetrazolium chloride (TTC) staining. Morphological changes in ischemic brains were performed for hematoxylin-eosin (HE) staining. The number of apoptotic neurons was detected by TUNEL staining. The Bax, Bcl-2 protein expression and CytC, Caspase-3, -9 and cleaved PARP-1 activation were investigated by immunofluorescence and western-blot analysis. RESULTS: LBP (10, 20 and 40 mg/kg) treatment groups significantly reduced infract volume and neurological deficit scores. LBP also relieved neuronal morphological damage and attenuated the neuronal apoptosis. LBP at the dose of 40 mg/kg significantly suppressed overexpression of Bax, CytC, Caspase-3, -9 and cleaved PARP-1, and inhibited the reduction of Bcl-2 expression. CONCLUSIONS: Based on these findings we propose that LBP protects against focal cerebral ischemic injury by attenuating the mitochondrial apoptosis pathway.